Pemanfaatan Artificial Intelligence sebagai Pendukung Asesmen Formatif dalam Pembelajaran IPA di Sekolah Dasar - Achmad Dwicky Fitra Utama; Amanda Widya Cahyani; Laras Permata Putri; Al Amida Rochma Fauziyyah; Tsabitah Aulia Farah (Prosiding Konferensi Ilmiah Dasar, 2026)
The development of  Artificial Intelligence (AI) has created various opportunities to enhance the quality of learning, including the implementation of formative assessments in primary schools. In Natural Science (IPA) education, formative assessment plays a crucial role in monitoring the development of student understanding, providing continuous feedback, and helping teachers determine instructional strategies tailored to students' needs. However, the implementation of formative assessment still faces obstacles, such as teachers' limited time for developing assessment instruments, providing individual feedback, and analyzing student learning outcomes. This article aims to describe the use of AI to support formative assessment in primary school science education, identify the benefits gained, and examine the challenges of its implementation. The study employs a literature review approach, analyzing relevant scholarly articles, books, proceedings, and policy documents concerning AI, formative assessment, and primary school science education. Data were analyzed descriptively through processes of data reduction, data presentation, and conclusion drawing. The findings indicate that AI can support the adaptive creation of assessment questions, provide faster and more personalized feedback, analyze student learning achievements, and assist teachers in identifying learning difficulties to design appropriate follow-up instruction. Beyond increasing the efficiency of formative assessment, AI also has the potential to foster learning that is more differentiated and student-centered. Nevertheless, AI implementation faces challenges such as limited teacher digital literacy, technological infrastructure readiness, personal data protection concerns, and the need for ethical guidelines regarding its use. Therefore, the use of AI should be positioned as a tool to support teacher professionalism rather than a replacement for the teacher's role in the learning process. Properly designed AI integration is expected to enhance the quality of formative assessment and support the creation of more effective, adaptive, and meaningful science learning in primary schools.